2010
DOI: 10.1021/ma101237u
|View full text |Cite
|
Sign up to set email alerts
|

RAFT-Mediated Emulsion Polymerization of Styrene with Low Reactive Xanthate Agents: Microemulsion-like Behavior

Abstract: Xanthates ([1-(O-ethylxanthyl)ethyl]benzene (CTA1) and [1-(O-trifluoroethylxanthyl)ethyl]benzene (CTA2)) have the capacity to control the molecular weight distribution in emulsion polymerizations to produce very small nanoparticles below 20 nm. We form stable translucent polystyrene latexes using surfactant (sodium dodecyl sulfate, SDS) and a small amount of pentanol as cosurfactant. The high CTA concentration results in a greater retardation in rate until consumption of all the RAFT agent. With an increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 86 publications
3
52
0
Order By: Relevance
“…In this context several groups have studied the kinetics of the RAFT emulsion polymerization of St [495,510] with xanthate RAFT agents. A detailed study of RAFT microemulsion of BA with xanthate RAFT agents has also been performed.…”
Section: Raft Polymerization In Heterogeneous Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…In this context several groups have studied the kinetics of the RAFT emulsion polymerization of St [495,510] with xanthate RAFT agents. A detailed study of RAFT microemulsion of BA with xanthate RAFT agents has also been performed.…”
Section: Raft Polymerization In Heterogeneous Mediamentioning
confidence: 99%
“…A* BA [125] 220 O S S F 3 C A* [495] (St) [495] 221 O S S A* (St) [495] (NES) [290] (BES) [290] (NVP) [103] NVC [496] (NVC-b-311) [496] NVC-b-314 [496] (Continued ) A NVP [103] 223 O S S G [103] (NVP) [103] …”
mentioning
confidence: 99%
“…1b) can be often assumed, strongly simplifying the overall kinetic description. 5,7,[30][31][32][33][34] A crucial design parameter, as for every RAFT polymerization, 15,16,35 is thus the selection of appropriate MADIX agent substituents as this determines C tr(,0) . For MADIX of MAMs, several kinetic studies have been performed with styrene as the monomer.…”
Section: Introductionmentioning
confidence: 99%
“…For MADIX of MAMs, several kinetic studies have been performed with styrene as the monomer. 7,17,19,25,32,34,36,37 For example, Adamy et al 7 investigated the influence of the chemical structure of the initial RAFT agent for MADIX of styrene in toluene and reported that with (O-ethyl xanthate)-2-ethyl propionate (OEXEP) as the initial RAFT agent, a Đ close to 2 (X m = 20%) can merely be obtained. In contrast, by increasing the electron-withdrawing capacity of the Z group by incorporation of fluorinated groups at β-position to the oxygen atom, as for instance in (O-2,2,2-trifluoro ethyl xanthate)-2-ethyl propionate (OtFOX), a lower but still high Đ of 1.6 can be achieved (X m > 20%), in agreement with an earlier experimental study by Destarac et al 36 The latter observation was attributed to an increased reactivity of the SvC bond due to the decreased availability of the oxygen lone pair to conjugate with the thiocarbonyl group.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few years, theoretical work has shown unequivocally that compartmentalization effects are anticipated in nitroxide-mediated radical polymerization (NMP), [11,12,14,15,[18][19][20][21][22][23] atom transfer radical polymerization (ATRP) [13,16,18,21,24,25] and reversible addition-fragmentation chain transfer (RAFT) polymerization [20,21,[26][27][28][29][30] if the monomer droplets/particles are sufficiently small. In many cases, these theoretical predictions have now been verified experimentally.…”
Section: Introductionmentioning
confidence: 99%